Contribution of integrative taxonomy to tracking interspecific hybridisations between the biological control agent Torymus sinensis and its related taxa. (18th May 2021) - Viciriuc, Ionela‐Mădălina; Thaon, Marcel; Moriya, Seiichi; Warot, Sylvie; Zhang, Jinping; Aebi, Alexandre; Ris, Nicolas; Fusu, Lucian; Borowiec, Nicolas
Abstract: Native to China, the chestnut gall wasps Dryocosmus kuriphilus Yasumatsu (Hymenoptera, Cynipidae) has invaded several countries on three continents in about half a century. To reduce the negative impact on the chestnut industry, the hymenopteran parasitoid Torymus sinensis Kamijo (Hymenoptera, Torymidae) was firstly translocated from China to Japan and then from Japan to other countries. From an agronomic point of view, this classical biological control programme is perceived as a great success story even if in Japan it was overshadowed by evidence of hybridisation with the indigenous species Torymus beneficus Yasumatsu & Kamijo. Based on numerous specimens collected in France and Italy but also in Asia, as well as on published data, we detected molecular and phenotypic signatures of a possible hybridisation. Our results evidenced for the first time that the European stock of T. sinensis has some rare molecular signatures of historical hybridisation that took place in Japan (0.66% of the mitochondrial haplotypes). Our morphometric study also shows that European and Japanese T. sinensis are morphologically intermediate between the two species that hybridised. The identity of the early‐ and late‐season strains of T. beneficus is discussed. Torymus beneficus late‐season strain (TbL) is considered to be the same as T. sinensis and only the early‐season strain (TbE) is the true T. beneficus . Torymus beneficus is morphologically very close to T. sinensis, and the interspecific distance of COI, though large, is comparable with the larger intraspecific variability found in other Chalcidoidea species. Though the two could be regarded as subspecies, for the stability of nomenclature it is better to continue treating them as distinct species. Abstract : European populations of Torymus sinensis have signs of hybridisation with Torymus beneficus that took place in Japan: 0.66% of the mitochondrial haplotypes are derived from T. beneficus (early‐spring strain). Multivariate ratio analysis shows that European Torymus sinensis are morphologically intermediate between Chinese T. sinensis and the type series of T. beneficus . Molecular and morphometric results show a high variability, indicating that T. sinensis populations were not affected negatively by the introduction program.